Implementation and use of risk minimization control tools in the EU: A multistakeholder survey - Sharon C. M. Essink; Iris R. Joosse; Maximilian Salcher‐Konrad; Melanie Walter; Elena Deligianni; Dimitra Tsioumela; Christos Kontogiorgis; Elita Poplavska; Iluta Žīgure; Christina E. Hoeve; Teresa Leonardo Alves; Ella D. van Vliet; et al. (British Journal of Clinical Pharmacology, 2026)
Aims This study characterized stakeholders' experiences with national implementation of risk minimization control tools (RMCTs), such as healthcare professional qualification, healthcare facility accreditation and medical intervention prior to treatment initiation, for eight medicinal products across eight European Union countries. Methods We conducted a cross‐sectional survey among national competent authorities, marketing authorization holders, physicians, pharmacists and other stakeholders involved in implementation or use of RMCTs in Austria, Greece, Latvia, the Netherlands, Portugal, Slovenia, Spain and Sweden. The following eight products were included: Aspaveli®, Fintepla®, Revlimid®/generics, Soliris®/biosimilars, Spravato®, Strimvelis®, Uptravi® and Yescarta®. Experiences were assessed across two implementation phases: regulatory implementation and integration into healthcare. Outcomes were perceived ease of implementation, barriers and enablers. Descriptive analyses were performed. Results We received 202 valid entries, representing 286 stakeholder‐product combinations. Experiences with regulatory implementation were heterogeneous. Approximately 75% of respondents rated regulatory implementation as difficult or very difficult for Fintepla® and Spravato®, compared with about 25% for Uptravi®. The complexity of RMCTs was a key barrier, while prior experience and peer learning were enablers. Integration into healthcare was predominantly perceived as easy, with easy or very easy ratings ranging from over 90% for Fintepla® and Spravato® to about 75% for Revlimid®/generics. Administrative effort was the main barrier, whereas clinical guidelines, training, peer learning and prior experience facilitated integration. Conclusions RMCT implementation was generally perceived as feasible, although regulatory implementation was more challenging than integration into healthcare. Successful implementation may benefit from flexible design, alignment with existing systems, feasibility assessment, stakeholder engagement and clear guidance.